Social Media Factors and Purchase Intention of Beauty Products in Mauritius - Lim, Kim Yew; Maysoon Hanaa, Mohamodhossen; Wong, Chee Hoo; Ng, Alex, Hou Hong; Tan, Owee Kowang (INTI International University, 2019)
Social media marketing has shown its impact when it comes to boosting e-commerce. However, there are very limited academic research focuses on the relationship between social media marketing and purchase intention of beauty products in Mauritius. The objectives of this research is to investigate Electronic Word of Mouth, Social Networking Sites and Mobile Applications and purchase intention. The study population involves 267 questionnaires filled by the female population via convenience sampling method. Multiple regression analysis is conducted using SPSS. The research finds significant positive relationship between Electronic Word of Mouth and Social Networking Sites with Purchase Intention. In this respect, beauty product seller could benefit from this research by obtaining better understanding on social media marketing strategies.